2022
DOI: 10.1021/acs.energyfuels.2c00592
|View full text |Cite
|
Sign up to set email alerts
|

Water Saturation and Distribution Variation in Coal Reservoirs: Intrusion and Drainage Experiments Using One- and Two-Dimensional NMR Techniques

Abstract: Determining water occurrence in pore-fracture systems under specific water saturation is of great significance to reveal the correlation between the water content and porosity/permeability of coal reservoirs. In this work, simulation experiments of water intrusion and drainage are used to study the micro-occurrence and migration of water using NMR T 2 and T 1 −T 2 techniques and discuss the influence of pore-fracture system structure parameters on water micro-occurrence. Meanwhile, water distribution heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 35 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Zhang et al 3,12 . shows that fractal models can be divided into single fractal and multi‐fractal models, and then a single model can be divided into three fractal dimension parameter, this is, D 1 ( T 2 is less than T 2 cut off , which represents smaller pore size distribution heterogeneity), D 2 ( T 2 is larger than T 2 cut off , which represents larger pore size distribution heterogeneity) and D 3 (represents total pore size distribution heterogeneity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 3,12 . shows that fractal models can be divided into single fractal and multi‐fractal models, and then a single model can be divided into three fractal dimension parameter, this is, D 1 ( T 2 is less than T 2 cut off , which represents smaller pore size distribution heterogeneity), D 2 ( T 2 is larger than T 2 cut off , which represents larger pore size distribution heterogeneity) and D 3 (represents total pore size distribution heterogeneity).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the T 2 spectrum in a saturated state, quantitative characterization of pore size distribution heterogeneity by using fractal theory has been studied. 3,10,11 Zhang et al 3,12 shows that fractal models can be divided into single fractal and multi-fractal models, and then a single model can be divided into three fractal dimension parameter, this is, D 1 (T 2 is less than T 2 cut off , which represents smaller pore size distribution heterogeneity), D 2 (T 2 is larger than T 2 cut off , which represents larger pore size distribution heterogeneity) and D 3 (represents total pore size distribution heterogeneity). Meanwhile, the relationship between different fractal parameters and pore structure, porosity-permeability parameters and mineral content are discussed, indicating that D 1 has a positive correlation with smaller pore volume, and the multi-fractal parameters have good applicability in characterizing pore structure heterogeneity of tight sandstone.…”
mentioning
confidence: 99%
“…When the researchers performed LF-NMR tests on watersaturated coal samples, they found that the higher the saturation pressure, the more fully the fluid can fill the pores, and the more NMR signal characteristics can represent the real pore characteristics. 26,27 Zhang et al 28 adjusted the saturation pressure of coal samples to 5, 10, and 15 MPa sequentially. However, when the saturation pressure was above 10 MPa, the variation of NMR signal became less and less obvious.…”
Section: Introductionmentioning
confidence: 99%
“…used LF-NMR to test the coal samples under confining pressure, and they found that pore volume did not decrease but increased and suggested that the reason may be that during the loading process, the pore volume shrunk and water migrated from micro- and minipores to meso- and macropores/fractures, resulting in an increased T 2 signal, which further caused the phenomenon of pore volume increase. When the researchers performed LF-NMR tests on water-saturated coal samples, they found that the higher the saturation pressure, the more fully the fluid can fill the pores, and the more NMR signal characteristics can represent the real pore characteristics. , Zhang et al adjusted the saturation pressure of coal samples to 5, 10, and 15 MPa sequentially. However, when the saturation pressure was above 10 MPa, the variation of NMR signal became less and less obvious.…”
Section: Introductionmentioning
confidence: 99%